The contradictions between anti-terrorism measures and the human rights in the context of the democratic States of Law (Emancipação, 2021)
Globalization, along with the benefits of technological advances, has brought with its new risks that are part of the so-called risk society. It is within this framework that terrorism forms in the contemporary format is inserted together with the generalized sense of insecurity or state of tension caused by it, especially after the attack in the United States on September 11, 2001. In response to this phenomenon, States have instituted measures that endanger human rights. Therefore, through a qualitative research, using the dialectic method, bibliographic and documentary survey, it has been carried out an analysis of the influences on the content and the way in which these measures are introduced in the legal systems, in general, which enabled the verification of the extent to which these are compatible with the current format of the Democratic State of Law, the product of a new constitutionalism, and with the very conception of human rights.
Keywords: Society of risk. Counter-terrorism measures. Democratic and Constitutional State of Law.